Mechanisms of the immune response cause by cationic and anionic surface functionalized cellulose nanocrystals using cell-based assays. (March 2019) - Despres, Hannah W.; Sabra, Adham; Anderson, Phil; Hemraz, Usha D.; Boluk, Yaman; Sunasee, Rajesh; Ckless, Karina
Abstract: The interest in functionalized cellulose nanocrystals (CNCs) for multiple biomedical application has been increasing in recent years. CNCs are suitable to functionalization with an array of polymers, generating chemically related nanomaterials with different morphologies, surface charges that can affect bioreactivity, including immune response. In this study, we sought to understand the mechanistic differences regarding immunological responses evoked by functionalized CNCs and whether surface charges play a role in this effect. We investigated the effect of a cationic, CNCs-poly(APMA), and an anionic, CNCs-poly(NIPAAm) derivatives on the secretion of inflammatory cytokines, mitochondria-derived ROS and mitochondrial function and antioxidant response as well as on endoplasmic reticulum (ER) stress, in human and murine inflammatory cells. The cationic CNCs-poly(APMA) evoked a more robust immunological response in murine cell line, while the anionic CNCs-poly(NIPAAm) showed a significant NLRP3 inflammasome-dependent and independent immunological response in human monocytes. Moreover, CNCs-poly(NIPAAm) induced greater formation of acidic vesicular organelles, mitochondrial ROS in non-stimulated cells while CNCs-poly(APMA) mainly affected mitochondrial function by decreasing the intracellular ATP. The differences on the biological responses may be related to the surface charges of CNCs, and their likely interactions with intra and extracellular biomolecules. Graphical abstract: Highlights: Both cationic and anionic functionalized cellulose nanocrystals evoked immune response in vitro. The extension of the immune response and the mechanisms diverge. The differences on the responses may be related to the surface charges of functionalized cellulose nanocrystals.